Eksplikasi Susunan Naratif oleh Andrea Hirata dalam Novel Buku Besar Peminum Kopi (Analisis Naratologi Perspektif Gérard Genette) - Faiza Fitria (Madah: Jurnal Bahasa dan Sastra, 2023)
A novel is a complex narrative structure that functions as an explication of reality of life in which  narratology analysis of Gérard Genette's perspective is an  appropriate literary theory to analyse it because it contains five theoretical components. This research applies descriptive qualitative research, note-taking technique for data collection, and partial-integral analysis to analyse the data. This study aims to describe the narrative structure (storytelling) and its analysis findings in the novel “Buku Besar Peminum Kopi” using the five components of Genette's narratology theory. The study show that the novel  “Buku Besar Peminum Kopi” has a mix of anachronism and achronim plot, three types of narrative duration (pauses, scenes, and ellipsis), three types of frequency (singular, anaphoric, and iterative). The narrator,  in the second level in this novel, acts as an observer, the point of view comes from the characters, and the story time is mixed i.e. past and present.